Multi-targeted potential of Pittosporum senacia Putt.: HPLC-ESI-MSn analysis, in silico docking, DNA protection, antimicrobial, enzyme inhibition, anti-cancer and apoptotic activity. (December 2019) - Mahomoodally, Mohamad Fawzi; Picot-Allain, Carene; Hosenally, M.; Ugurlu, Asli; Mollica, Adriano; Stefanucci, Azzurra; Llorent-Martínez, E.J.; Baloglu, Mehmet Cengiz; Zengin, Gokhan
Graphical abstract: Highlights: Pittosporum senacia was evaluated for biological effects as well as chemical profiles. Antioxidant, enzyme inhibition, antimicrobial and cytotoxic effects were investigated. Apoptotic genes and in silico approach was performed. Caffeoylquinic acid derivatives were the most abundant in the extract. Pittosporum senacia could be a promising source of novel source of therapeutic compounds. Abstract: Pittosporum senacia (PS) Putt. (Pittosporaceae), indigenous to the Mascarene Islands, is a common ingredient in traditional medicines. However, there is currently a dearth of studies to validate some of these traditional claims. Given the broad traditional uses of PS against several diseases, we aimed to provide a comprehensive insight into the biological and chemical profile of P. senacia . The antioxidant, enzyme inhibitory activity, anticancer, and phytochemical composition of the methanolic extract of P. senacia leaf extracts were studied. The possible interaction and binding mode of the most abundant phytochemicals were studied via in silico docking experiments on tyrosinase and α-glucosidase. The mechanism behind the cytotoxic property of P. senacia extract for MDA-MB-231 was also examined using different methods including 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) cell viability test checking apoptosis-associated genes, and wound healing assays. Twenty-six compounds were identified, of which caffeoylquinic acid derivatives, ferulic acid derivative, cinnamoylquinic acid derivative and two other polyphenols (oleuropeine and isoramnetin glucoside) being abundant, have been tested using in silico studies, against α-glucosidase and tyrosinase. The extract (IC50  = 118.8 μg/ml) exhibited time and dose dependent anti-proliferative effect on human breast cancer cell line, MDA-MB-231. According to the expression profile of apoptosis inhibitors and apoptosis promoters genes, expression of Bax and Bak genes were significantly increased compared to Bcl-2 and Birc5 genes. Based on wound healing analysis, cell migration was inhibited after the application of the plant extract. The present findings suggested that PS might be a good candidate as sources of bioactive compounds for designing functional applications.